Staff Training as Determinant of Job Performance of Librarians in Public Universities in Southern Nigeria - Fabunmi, Samuel Olabode; Ikonne, Chinyere N.; Madukoma, Ezinwanyi (Communicate: Journal of Library and Information Science, 2023)
This study was carried out to investigate staff training as determinant of job performance of librarians in public universities in Southern Nigeria. The survey research design was adopted for this study. The academic librarians in public universities in Southern Nigeria formed the population of the study. Total enumeration sampling technique was used for the study. A total of 571 questionnaires were distributed across the universities with a retrieval success of 464 copies, representing 81.3% return rate. Data were analysed using percentages and linear regression analysis. The findings of this study revealed that there is a high level of staff training in public universities in Southern Nigeria (mean=34.68). It was equally revealed that the level of job performance of librarians in Southern Nigeria was high(mean=84.49) as librarians indicated that their personal discipline, (¯x= 3.66), teamwork (¯x= 3.64), job specific task (¯x= 3.62) and non-job specific task ((¯x= 3.50) was high. Findings further showed that staff training significantly influenced the job performance of librarians in universities in Southern, Nigeria (R2 = 0.502, β = 0.708, t (462) = 21.187, p < 0.05). Staff training serves as a medium to acquire more skills and experience which enable the librarians to be a good performer at work place. It was recommended that the university management should prioritize the training and development of their librarians by providing regular staff training programs, workshops, and seminars. This will enable librarians to acquire the necessary skills and knowledge to improve their job performance by the university management.